Analysis of Word Formation Process in Register Used by English and Indonesian Football Commentary - Wiwiek Sundari; Muhammad Faizal M. (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2023)
This study examines the use of register and word-formation in football commentary, focusing on Indonesian and English commentators. With European countries being the center of the football industry, studying the commentary from these languages can provide insights for other countries, including Indonesia. The aim of this research is to identify the application of register and classify word-formation patterns in Indonesian and English football commentary. Linguistic theories from experts such as George Yule, Katamba, O’Grady and Guzman, and Stockwell and Minkova are utilized. A descriptive qualitative research method is employed, analyzing video documentation of matches using Simak Bebas Libat Cakap (SLBC) to collect data. The findings reveal 78 word formations in both Indonesian and English commentary, with compounding and coinage being the most frequent processes. The word-formation analysis found compounding, coinage, borrowing, derivation, reduplication, and abbreviation. Differences and similarities are observed in terms of word usage, word-formation patterns, and the background factors influencing them.